An Analisis Epistemological Obstacle Berdasarkan Kesalahan Menyelesaikan Soal Matematika Materi Segitiga Siswa Kelas VII SMP Negeri 3 Mataram Tahun Ajaran 2022/2023 - Ainun, Yusri; Sridana, Nyoman; Kurniati, Nani; Sarjana, Ketut (Mandalika Mathematics and Educations Journal, 2024)
This research aims to describe epistemological obstacles based on errors in solving mathematics problems related to triangle material for class VII students at SMP Negeri 3 Mataram. This research method uses a qualitative descriptive method with data collection methods including diagnostic tests and questionnaires. The sample was selected from class VII-4 of SMP Negeri 3 Mataram where the sample search method was carried out using tests. Determination of the sample using a purposive sampling technique. The sample selected was six students based on the results of tests and grouped into three groups with each group consisting of 2 students in the high, medium, and low error category and then given a questionnaire. The results of the research show that the types of epistemological obstacles experienced by students are conceptual epistemological obstacles with a percentage of 56.99%, procedural epistemological obstacles with a percentage of 95.70%, and operational technique epistemological obstacles with a percentage of 79.57%. For students with a high error category, the percentage of conceptual epistemological obstacles is 100%, procedural epistemological obstacles are 100%, and operational technique epistemological obstacles are 100%. Meanwhile, for students with the moderate error category, the percentage of conceptual epistemological obstacles was 66.67%, procedural epistemological obstacles were 100%, and operational technique epistemological obstacles were 89.86%. Finally, for students in the low error category, the percentage of conceptual epistemological obstacles was 5.56%, procedural epistemological obstacles were 72.22%, and operational technique epistemological obstacles were 33.33%.